Multi-hazard resistance capacity of precast segmental columns under impact and cyclic loading - Zhang, Xihong; Hao, Hong; Li, C. (Multi-Science Publishing Co. Ltd., 2018)
Using precast segmental concrete columns in structures improves the construction efficiency and site safety, leads to better construction quality, and reduces the construction cost, site disruption and environmental impact. The performance of segmental columns to resist earthquake and impact loads is not well studied yet. As a structure might be subjected to such loads during its service life, understanding its resistance capacities is essential for structural safety. This article reports the findings of our recent studies on the response of precast segmental columns with unbonded prestress tendons. Pendulum impact test and uniaxial cyclic test were conducted on quarter-scale segmental columns. The seismic performance and impact-resistant capacity were evaluated experimentally and compared with a reference conventional monolithic column. Test results showed that under cyclic loading, segmental columns exhibited better deformation ability and smaller residual drift; under impact loading, segmental columns also showed better self-centring capacity and less residual displacement. By introducing concrete shear key, the shear resistance at segmental joint could be improved; however, shear key would also result in more concrete segment damage owing to stress concentration.